The Symbolic Dimensions of the Child’s Image in Naji Al-Ali’s Caricatures - Ishtia, Dr. Moaz (Thi Qar Arts Journal, 2024)
There is no doubt that there are many studies and researches that have taken care of researching Naji Al-Ali’s caricatures; however, the researcher often finds that they focused more on the contents and themes rather than delving into their artistic structure. These studies addressed the issues that Al-Ali was concerned with without researching the dimensions behind these issues. Hence, this study comes to explore the symbolic dimensions that contribute to deepening the vision expressed by the caricature image of Naji Al-Ali. This research direction contributes to the textual analysis of the caricature panel, without entering into general judgments. The caricature discourse, like many creative discourses, comes loaded with human, cultural, political, and social dimensions, and uncovering these connotations can only be through researching the caricature text as coherent elements of symbols represented by visual, linguistic, and numerical systems.